Follow-Up of the Immune Response and the Possible Presence of Brucella melitensis Strains in Peripheral Blood in Hoggets Vaccinated by Rev1 in Greece - Maria Babetsa; Hanka Brangsch; Gamal Wareth; Ilias Bouzalas; Athanasios I. Gelasakis; Antonios Zdragas; Loukia V. Ekateriniadou; Evridiki Boukouvala; Athanasios I. Papadopoulos (Microbiology Research)
Brucellosis in small ruminants, primarily caused by B. melitensis, remains a significant threat to public health in many regions. Although early-age vaccination of breeding stocks was expected to facilitate infection control, this approach did not meet expectations, while in some cases, late vaccination of animals has been associated with an increased number of human cases. Therefore, in this field study, we investigated the immune response and bacteremia cases in ten apparently healthy hoggets vaccinated at the age of nine months. Before vaccination, the hoggets were seronegative and negative in blood cultures, although B. melitensis DNA was detected in three animals using PCR. After vaccination, twelve Brucella spp. strains were isolated from the blood cultures of nine hoggets at different time points. Whole genome analysis identified eleven of them as identical to three B. melitensis strains previously isolated in Greece. The tested animals completed their gestation without any adverse outcomes. According to our results, late vaccination, despite extending animal exposure to B. melitensis, apparently protects against disease and abortion but not against infection. The onset of post-vaccination immune response may be influenced by transient infections by field strains.